2014
DOI: 10.4103/0976-9668.136200
|View full text |Cite
|
Sign up to set email alerts
|

Recent trends in the spectrum of opportunistic infections in human immunodeficiency virus infected individuals on antiretroviral therapy in South India

Abstract: Background:Opportunistic infections (OI) are the major cause of morbidity and mortality among human immunodeficiency virus (HIV) infected individuals. The pattern of OIs differs widely, hence it is necessary to correlate spectrum of OIs and CD4 counts among HIV infected individuals in specific localities.Materials and Methods:The present study describes the clinical and laboratory profiles of different OIs among 55 HIV seropositive patients. CD4 count was estimated and antiretroviral therapy (ART) was started … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
20
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 16 publications
3
20
1
Order By: Relevance
“…Kumarasway et al in his study reported a higher prevalence of extra pulmonary tuberculosis (49%) than pulmonary which is contrary to the findings of our study. 16 Mean CD4 count observed in cases of pulmonary tuberculosis in our study was 74.5 (1-312) cells/µl, extra pulmonary tuberculosis was 67.5 (1-276) cells/µl and 65.5 (1-254) cells/µl in cases of both, these findings are on par withfindings of Shahapur PR et al 17 The HIV positive patients with extra pulmonary tuberculosis had lower mean CD4 counts than those with pulmonary tuberculosis.Some studies reported candidiasis as the most common OI in their studies. In our study, it was second most common OI with prevalence of 61.5%, with oral thrush 87.8% and esophageal candidiasis in12.2%, which is on par with findings of Singh et al (59%), and several studies have reported the incidence up to 70%.…”
contrasting
confidence: 48%
“…Kumarasway et al in his study reported a higher prevalence of extra pulmonary tuberculosis (49%) than pulmonary which is contrary to the findings of our study. 16 Mean CD4 count observed in cases of pulmonary tuberculosis in our study was 74.5 (1-312) cells/µl, extra pulmonary tuberculosis was 67.5 (1-276) cells/µl and 65.5 (1-254) cells/µl in cases of both, these findings are on par withfindings of Shahapur PR et al 17 The HIV positive patients with extra pulmonary tuberculosis had lower mean CD4 counts than those with pulmonary tuberculosis.Some studies reported candidiasis as the most common OI in their studies. In our study, it was second most common OI with prevalence of 61.5%, with oral thrush 87.8% and esophageal candidiasis in12.2%, which is on par with findings of Singh et al (59%), and several studies have reported the incidence up to 70%.…”
contrasting
confidence: 48%
“…(18)(19) Our finding also corresponds with studies done earlier in India in both the northern and southern regions. (20)(21) Concomitant bacterial (44.6%) and fungal pneumonia (31.9%) is a significant finding in our study. In such cases, the dilemma for the clinician is to decide whether to treat the positive Pneumocystis finding as an infection or merely colonization.…”
Section: Discussionsupporting
confidence: 65%
“…Saha et al [24] showed that the common co-infections/OIs were oral candidiasis followed by chronic diarrhea, HSV-2, TB, CMV, HBV, and HCV, while Elizabeth et al [25] showed that the most common OIs were oropharyngeal candidiasis followed by TB. In the study by Shahapur et al, [26] pulmonary TB was the most common OI, followed by candidiasis, cryptosporidial diarrhea, herpes zoster, cryptococcal meningitis, and pneumocystis pneumonia.…”
Section: |Discussionmentioning
confidence: 93%